Migratory Trajectories: Determinations of Inward and Outward Movement in India. Issue 1 (January 2015) - Joshi, Tarun; Deb, Roumi
For a country like India whose cultural and economic dimensions vary a lot, it is important to understand the impetus or motivation behind any movement which is on record or not. Internal migration has its own routes and thresholds which may differ from region to region. The basic interest of the movement is prosperity and better life standards, however, the definition of these vary according to the standards predisposed in mind. In general it is been preconceived and also supported by census of India that men migrate more often than women on grounds of employment but studies have shown that there is a shift and women are the one who migrates maximum outnumbering men in many cases. But it is a pity that national level large scale surveys are unable to capture this reality as a result women are treated as secondary earners International migration to and from India have its own pros and cons. Immigration provides cheap labour and strengthen political bonds between party nations, while on the other hand emigration bring foreign exchange to the country. The definition of status is also radically altered by the effect of social meaning of migrant remittances. The emigrants are preferred as a marriage partner in many parts of India especially Punjab which has even lead to the increasing cases of fraud on marital grounds.